Stable reflective state induced by a disturbed planar texture in surface-treatment-free chiral nematic liquid crystals - Chen, Hui-Yu; Tsao, Yu-Chuan; Chang, Chin-Hao; Chen, Jui Jiun (Optics express, 2021)
Chiral nematic liquid crystals possess a one-dimensional periodic helical structure and are one of the oldest known materials with the ability of selective reflection of light. Their helix orientation, determining their optical properties, can be changed by a variety of stimuli, and it is also dominated by the surface treatment, ratio of the elastic constants and cell thickness. Here, we present a simple method to realize an angular independence reflective state, induced by a stable disturbed planar texture, in a surface-treatment-free chiral nematic liquid crystal cell. The scattering state caused by the defect-rich focal-conic texture can be electrically tuned to the reflective state from the disturbed planar texture in a very short time, and vice versa. These two optical conditions are both stable states in the null field until the next trigger. We find that the disturbed planar texture in the chiral nematic can provide a 100° viewing angle without reflected wavelength shift. The gray level of the reflected intensity can be tuned via application of the voltage pulses. Moreover, in this work, we discuss the effect of the chiral concentration on stabilizing the disturbed planar texture. When the chiral concentration is higher to induce the blue phases, the change in the texture of the ChNLCs after removing the strong electric field can stop at the disturbed planar texture with high reflectivity. In this work, the optical performance and the bistability based on the disturbed planar texture exhibits great potential for many applications, such as tunable filters, see-through/reflective displays and large-area smart windows.